Hierarchical distributed model scheme implementation in DC μgrid for numerous ground faults condition - Yuvaraja, T; Ramya, K (International journal of electrical engineering & education, 2019)
This article presents a new protection scheme for the µgrid structure is implemented on low voltage side as DC system’s protection methods are quite new when compared to the AC systems. The protection system designed in AC system faces many difficulties like frequency matching, reactive power violation, and instability. The main objective of the proposed system is to eliminate the faulty segment promptly while keeping the healthy segments functioning unaltered. In the proposed method, a unitwise controller is designed and is connected in feedback so as to maintain stability under all conditions. The unitwise controller comprises primary and secondary controllers which continually monitor all the units of DC grid comprising semiconductor bidirectional switches and snubber circuits. A primary controller is used for monitoring the complete variation in the parameters in all the units. If the observed parameter value is greater than the acceptable range, the secondary controllers receive the command so as to take the required action to eliminate the faulty segment. Both lines and ground faults are tested on all the sections separately and also simultaneously. The tested results are analyzed in all aspects and the results of the states that the designed protection scheme competent in isolating the defective segment within a short period of time. Once the defective segment is isolated, the other segments retain the stabilized voltage and current limits. The protection scheme is designed and verified using MATLAB/Simulink.